How to kill your neighbor's dog [videorecording (DVD)] - Kalesniko, Michael, 1961-; Branagh, Kenneth; Wright, Robin, 1966-; Harris, Jared, 1961-; Schaech, Johnathan, 1969-; Krumholtz, David, 1978-; Riegert, Peter, 1947-; Redgrave, Lynn, 1943-2010 (Key DVD, 2003)
"In the midst of writing a new play, Peter McGowen's world is one crazy scene after another. He has a wife who desperately wants to start a family, a stalker who's assuming his identity and a crisis which is a scribe's worst nightmare: writer's block. To top it all off, he's pushed to the edge by the barking dog next door. Peter only has time for his writing, until a special new neighbor teaches the cynical playwright that life is a work in progress"--Container.